Keratoconus as a manifestation of connective tissue dysplasia - M. M. Bikbov; V. K. Surkova; K. Kh. Oganisyan (Oftalʹmologiâ, 2015)
Common association of keratoconus and connective tissue dysplasia indicates that these disorders possibly share etiology and pathogenesis. Connective tissue dysplasia is characterized by the decrease in certain types of collagen, abnormalities of their proportion, alteration of collagen synthesis and assembly, immature collagen synthesis, abnormalities of collagen fiber structure, defects of type III collagen synthesis, peptidase deficiency, and increase in pro-collagen as compared with collagen. The latter accounts for immature collagen level increase in tissues and organs and systemic congenital laxity of connective tissue. This results in the abnormalities of biomechanical properties of organs and tissues which are composed of collagen fibers. Corneal stroma consists of collagen fibers and glycoprotein matrix. Hence, quantitative and qualitative changes in connective tissue dysplasia affect corneal biomechanics. Abnormalities of collagen fibril orientation result in their reorganization thus influencing corneal shape and transparency. In keratoconus, decreased total collagen and type I, type III, and type IV collagen, increased type XV collagen, and abnormalities of their proportion in corneal stroma as well as allele differences in COL4A3 and CoL4A4 genes encoding 2 of 6 α-chains of type IV collagen were demonstrated. Nucleotide polymorphisms in LOX genes encoding lysyl oxidase and lysyl oxidase-like enzymes which are responsible for cross-linking of collagen polypeptide chains (and, therefore, mechanical strength of fibrils) were revealed as well. LOX gene deficiency that accounts for systemic biomechanical abnormalities was also recognized in certain connective tissue dysplasia. Further studies will provide early diagnosis and pathogenically target therapy of genetic disorders associated with tissue abnormalities